Wide diversity of parasites in Bombus terrestris (Linnaeus, 1758) revealed by a high‐throughput sequencing approach. (4th December 2020) - Bartolomé, Carolina; Jabal‐Uriel, Clara; Buendía‐Abad, María; Benito, María; Ornosa, Concepción; De la Rúa, Pilar; Martín‐Hernández, Raquel; Higes, Mariano; Maside, Xulio
Summary: Assessing the extent of parasite diversity requires the application of appropriate molecular tools, especially given the growing evidence of multiple parasite co‐occurrence. Here, we compared the performance of a next‐generation sequencing technology (Ion PGM ™ System) in 12 Bombus terrestris specimens that were PCR‐identified as positive for trypanosomatids (Leishmaniinae) in a previous study. These bumblebees were also screened for the occurrence of Nosematidae and Neogregarinorida parasites using both classical protocols (either specific PCR amplification or amplification with broad‐range primers plus Sanger sequencing) and Ion PGM sequencing. The latter revealed higher parasite diversity within individuals, especially among Leishmaniinae (which were present as a combination of Lotmaria passim, Crithidia mellificae and Crithidia bombi ), and the occurrence of taxa never reported in these hosts: Crithidia acanthocephali and a novel neogregarinorida species. Furthermore, the complementary results produced by the different sets of primers highlighted the convenience of using multiple markers to minimize the chance of some target organisms going unnoticed. Altogether, the deep sequencing methodology offered a more comprehensive way to investigate parasite diversity than the usual identification methods and provided new insights whose importance for bumblebee health should be further analysed.